Development of an indigenous bacterial consortium for enhanced oil degradation in saline-contaminated soils - Tuyen, Do Thi; Thuy, Tran Thi Thanh; Thanh, Nguyen Thi Kim; Cuong, Nguyen Viet; Loi, Nguyen Thi Thanh; Tien, Phi Quyet; Cuong, Ngo Cao (Brawijaya University, 2025)
This study developed the indigenous CR3.M3 bacterial consortium to enhance oil degradation in saline-contaminated soils. Seven hydrocarbon-degrading strains-closely related to Pseudomonas, Bacillus, and Niveispirillum species (92-99% 16S rRNA sequence similarity)-were isolated from polluted coastal soils using mineral salt media supplemented with crude oil and diesel. While phylogenetic analysis suggests close relationships to known oil-degrading species, formal taxonomic classification requires further genomic validation. The consortium degraded 70% of hydrocarbons within 13 days under saline conditions (?3% NaCl). Field trials in non-sterilized soils (3,542 mg/kg TPH) achieved 65.42% oil removal alongside microbial density increases from 6.26 to 8.11 Log??(CFU/g), confirming ecological compatibility. Its performance in both sterilized and native soils highlights adaptability for coastal bioremediation. Future research should optimize strain ratios, resolve taxonomic identities through whole-genome sequencing, and assess long-term ecological impacts to advance this sustainable remediation strategy.